Novel simulation framework of three-dimensional skull bio-metric measurement - Hameed, Shihab A.; Zaidan, B.B.; Zaidan, A.A.; Naji, Ahmed Wathik; Faroq, Omar (Engg Journals Publications, 2009)
Previously, most of the researcher was suffering from simulate any three dimension applications for biometrics application, likewise, various applications of forensics and cosmetology has not been easy to be simulated. Three dimensional figures have approved the fact that, it has been more reliable than two dimensional figures in most of the applications used to be implemented for the purposes above. The reason behind this reliability was the features that extract from the three dimensional applications more close to the reality. The goal of this paper is to study and evaluate how far three-dimensional skull biometric is reliable in term of the accurate measurements, capability and applicability. As it mentions above, it was hard to evaluate or simulate an application use three-dimensional skull in biometric, however, Canfield Imaging Systems provide a new suitable environment to simulate a new three-dimensional skull biometric. The second goal of this paper is to assess how good the new three-dimensional image system is. This paper will also go through the recognition and verification based on a different biometric application. Subsequently this paper will study the reliability and dependability of using skull biometric. The simulation based on the three-dimensional Skull recognition using three-dimensional matching technique. The feature of the simulate system shows the capability of using three-dimensional matching system as an efficient way to identify the person through his or her skull by match it with database, this technique grantee fast processing with optimizing the false positive and negative as well .